Mastering spring application development : gain expertise in developing and caching your applications running on the JVM with spring - Mankale, Anjana (Community experience distilled., 2015)
Chapter 4: Jobs with Spring Batch; Introduction to Spring Batch; Use cases for using Spring Batch; Goals of batch processing; Architecture of a batch job; Using an enterprise batch; Dependency for Spring Batch; Key components of Spring Batch; Developing a sample batch application; Creating a sample batch application using the Tasklet interface; Using Spring Batch to read a CSV file ; Spring Batch with a Spring scheduler; Configuring Spring Batch with Quartz scheduler; Using Spring Batch to read a file and update a MongoDB database; Using Spring Batch with threads to partition jobs.